2021
DOI: 10.3389/fpls.2021.765041
|View full text |Cite
|
Sign up to set email alerts
|

The Mixed Addition of Biochar and Nitrogen Improves Soil Properties and Microbial Structure of Moderate–Severe Degraded Alpine Grassland in Qinghai-Tibet Plateau

Abstract: The degradation of the grassland system has severely threatened the safety of the ecological environment and animal husbandry. The supplement of key substances lost due to degradation is widely used to accelerate the restoration of the degraded grassland ecosystem. In this study, we investigated the effects of biochar and nitrogen addition on soil properties and microorganisms of degraded alpine grassland. The experimental treatments consisted of the control without any addition, only nitrogen addition (10 gN/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Additionally, a positive correlation occurred between a majority of the environmental factors and ectomycorrhizal fungi and saprophytic fungi. This suggested that ectomycorrhizal and saprophytic fungi were particularly vulnerable to soil environments alterations in comparison to other indicator microorganisms, and they possessed a competitive edge ( Li et al, 2021 ). The Mantel test revealed a significant correlation between NH 4 + -N and different microbial communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a positive correlation occurred between a majority of the environmental factors and ectomycorrhizal fungi and saprophytic fungi. This suggested that ectomycorrhizal and saprophytic fungi were particularly vulnerable to soil environments alterations in comparison to other indicator microorganisms, and they possessed a competitive edge ( Li et al, 2021 ). The Mantel test revealed a significant correlation between NH 4 + -N and different microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…The climate of experimental region is typical plateau continental climate with mean annual temperature of 2.3°C and mean annual precipitation of 403.80 mm. The annual evaporation is 1378.5 mm ( Li et al, 2021 ). The main plants in the experimental site include Poa crymophila , Cleistogenes squarrosa , Carex tristachya , Elymus nutans .…”
Section: Methodsmentioning
confidence: 99%
“…The grasslands at Tibetan Plateau are vulnerable to damage due to short plant growth periods, harsh climate, and weak ecosystem resistance (Liu et al, 2018). The degradation of grassland thus will lead to severe ecosystem imbalance (Li et al, 2021), such as the decrease of vegetation biodiversity (Dong et al, 2013), loss of soil fertility (Hopping et al, 2018), and reduction of grassland productivity and ecological function diversity (Peng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the Qinghai‐Tibet Plateau, the main ecosystem is the alpine steppe ecosystem, which stores a large amount of carbon and plays an important role in the global carbon cycle (Li, Zhao, et al, 2021; Liu et al, 2016; Ni, 2002). The primary form of resource utilization in alpine grasslands on the Tibetan Plateau is grazing, which plays a dominant role in maintaining local livestock production and the sustainable development of pastures (Guo, Wen, et al, 2021; Li, Liu, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%